(untitled) (Applied Biological Research, 2025)
The colour of ornamental fish significantly influences their market value, with Koi carp (Cyprinus carpio) being globally admired for their vibrant patterns. Palash flower (Butea monosperma), commonly known as the flame of forest, is a natural carotenoid source abundantly available during April–May in Midnapore, Bankura, and Purulia districts of West Bengal, India. During flowering, large quantities of flowers fall to the ground and often go to waste. This study evaluated the effect of dietary incorporation of palash flower powder on the skin and muscle pigmentation of Koi carp. The 60-day indoor aquarium experiment involved six groups: T1 (control, no supplementation), T2 (2.5%), T3 (5%), T4 (7.5%), T5 (10%), and T6 (commercial feed). Fish were fed twice daily at 4% of body weight, with experimental feeds prepared using Pearson’s square method. Pigment concentration was determined spectrophotometrically. The highest total carotenoid content in skin (25.09 ± 0.20 µg g⁻¹) and muscle (15.78 ± 1.6 µg g⁻¹) was observed in T4 (p < 0.05), which also recorded the highest specific growth rate, weight gain, and 100% survival. Results indicate that 7.5% palash flower supplementation offers optimal pigmentation, growth performance, and cost-effectiveness compared to control and commercial diets.